2019
DOI: 10.1021/acscatal.9b03089
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Regioselectivity of B(C6F5)3-Catalyzed Epoxide Alcoholysis Reactions Using Hydrogen-Bond Acceptors

Abstract: Epoxide alcoholysis is extensively employed in the synthesis of polymers and chemical intermediates, and it generally requires an acid catalyst for high rates and selectivity. Tris­(pentafluorophenyl)­borane [B­(C6F5)3] is among few catalysts that are selective to primary alcohol products of terminal aliphatic epoxides that do not possess any directing groups. We have previously observed that under many conditions, the reaction regioselectivity increases with conversion. Here, we confirm a prediction from our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 70 publications
6
17
0
Order By: Relevance
“…Parameters VI and VII, which account for the second-generation RO reactions by P1 or P2 that occur at high epoxide conversion, indicated that P1 is more reactive than 1Prop, while P2 is less reactive than 1Prop as a nucleophile. Stated otherwise, 1Prop-derived P1 preferentially forms larger oligomers, consistent with Figure and our companion work . Thus, in the absence of oligomerization, the selectivity to P1 would be even higher than observed experimentally in the 1Prop system.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Parameters VI and VII, which account for the second-generation RO reactions by P1 or P2 that occur at high epoxide conversion, indicated that P1 is more reactive than 1Prop, while P2 is less reactive than 1Prop as a nucleophile. Stated otherwise, 1Prop-derived P1 preferentially forms larger oligomers, consistent with Figure and our companion work . Thus, in the absence of oligomerization, the selectivity to P1 would be even higher than observed experimentally in the 1Prop system.…”
Section: Resultssupporting
confidence: 89%
“…The results here show that a model with only a Lewis acid pathway is not sufficient to describe the system because the pronounced dependence of product selectivity on reaction conditions (e.g., water concentration) that we have observed is not possible to be captured by any model that uses a single kinetically relevant pathway. In contrast, our triple-pathway mechanism is robust enough to capture reactivity trends across a wide range of conditions and to provide hypotheses about deliberately added species that could beneficially influence the reaction selectivity, as we discuss in our companion manuscript …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We then tested abulky Lewis acid, namely B(C 6 F 5 ) 3 . [22] Gratifyingly,t he reaction in dichloromethane afforded the homoallylic alcohol with excellent yield (82 %) and selectivity (3a/4a:98:2, entry 8). With this result in hand, we performed asolvent screening.…”
Section: Resultsmentioning
confidence: 99%